A Mathematical Formulation to Estimate the Effect of Grain Refiners on the Ultimate Tensile Strength of Al-Zn-Mg-Cu Alloys - Kurt, Halil Ibrahim; Oduncuoglu, Murat; Kurt, Mehmet (Mdpi Ag, 2015)
In this study, the feed-forward (FF) neural networks (NNs) with back-propagation (BP) learning algorithm is used to estimate the ultimate tensile strength of unrefined Al-Zn-Mg-Cu alloys and refined the alloys by Al-5Ti-1B and Al-5Zr master alloys. The obtained mathematical formula is presented in great detail. The designed NN model shows good agreement with test results and can be used to predict the ultimate tensile strength of the alloys. Additionally, the effects of scandium (Sc) and carbon (C) rates are investigated by using the proposed equation. It was observed that the tensile properties of Al-Zn-Mg-Cu alloys improved with the addition of 0.5 Sc and 0.01 C wt.%.
Keywords: B Master Alloys; Artificial Neural-Network; Mechanical-Properties; Aluminum-Alloys; Al-20-Percent-Mg Alloy; Compressive Strength; Microstructure; Ti; Sc; Zr